Emerging Market of Nepalese Mutual Fund in Nepal: A Systematic Review - Bajracharya, Rajan Bilas; Aithal, P. S. (International Journal of Atharva, 2024)
The aim of this research was to determine the current state of the Nepalese mutual fund developing market. Studies carried out between 2010 and 2023 show that the specific topic area has been investigated. The research's dataset comprised 21 articles published in Nepal during a 14-year span.  In the review of Researchers found that time restrictions and insufficient information provide obstacles for investors. Risk division is provided by mutual funds, along with other advantages including cash flow, accessibility, efficiency, creativity, and prevention. The safety and liquidity of funds impact investors' opinions of mutual fund investments. Advantages of mutual funds include cost-effectiveness, accessibility, personalization, innovation, transparency, and prevention when it comes to risk segmentation.